The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7717/peerj.13935
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of inner cell mass: a better predictive biomarker of blastocyst viability

Abstract: Background Transfer of embryos at the blastocyst stage is one of the best approaches for achieving a higher success rate in In vitro fertilization (IVF) treatment as it demonstrates an improved uterine and embryonic synchrony at implantation. Despite novel biochemical and genetic markers proposed for the prediction of embryo viability in recent years, the conventional morphological grading of blastocysts remains the classical way of selection in routine practice. This study aims to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Given that blastocysts generated from sperm exposed to all concentrations of THC had fewer ICM cells, and that ICM quality is highly predictive of pregnancy and implantation rates [ 137 ], paternal cannabis use would be expected to adversely affect IVF outcomes. However, current clinical research shows no associations between paternal cannabis use and implantation rates or time to pregnancy [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that blastocysts generated from sperm exposed to all concentrations of THC had fewer ICM cells, and that ICM quality is highly predictive of pregnancy and implantation rates [ 137 ], paternal cannabis use would be expected to adversely affect IVF outcomes. However, current clinical research shows no associations between paternal cannabis use and implantation rates or time to pregnancy [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these data suggest that the materials printed with stereolithography (PEGDAs) are less biocompatible than extrusion-printed materials (PLA and PCL). On the other hand, the TCN, the ICM/TE ratio and the ACR are three important parameters of embryo quality and in recent years, several studies have shown that the rate of ICM/TE is a strong predictor of live birth ( Ai et al, 2021 ; Sivanantham et al, 2022 ). When we analyzed all these parameters, the principal component analysis (PCA) showed that the embryos produced in presence of PLA and PCL scaffolds are the most comparable to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Both model experiments and field trials of possible antibiotic alternatives in different livestock production systems are considered necessary to address these challenges (Callaway et al, 2021). Such research should be effective if it is based on the study of fundamental indicators, namely, molecular markers of central pathways for cellular functions control and whole organism viability support (Sivanantham et al, 2022).…”
Section: Discussionmentioning
confidence: 99%